Crescimento inicial e diversidade genética em progênies de Zeyheria tuberculosa (Vell.) Bureau (Bignoniaceae) - Assunção, Raul Reis (2022)
Despite the wide Brazilian biodiversity, the number of native forest species used in genetic breeding and forestry programs is still scarce. Even though its economic value for the timber market is recognized, their exploration in natural forests, mostly illegally, continues to be more common than commercial plantations, reducing the number of individuals and their genetic basis in natural biomes. Among numbers of species with high potential for domestication, Zeyheria tuberculosa (ipê-felpudo) stands out as a Bignoniaceae family species, native from the Atlantic Forest and Cerrado biomes, classified as vulnerable to extinction and which presents a series of favorable characteristics for domestication, such as: fast growth, monopodial growth, good stem shape, easy seedling production and wood of noble quality. With the purpose of contributing to its genetic breeding, the present work aims to estimate genetic parameters for initial growth’s characters and to quantify the genetic diversity and structure in Zeyheria tuberculosa progenies, as a subsidy for early selection and seedling seed orchards formation. The experiment contains 71 progenies and was installed in the municipality of Ijaci-MG, in a randomized block design, with 15 replications, resulting in 1065 single-plant plots in total. At 15 and 21 months old, data on height (ALT), diameter at ground height (DAS) and survival (SOB%) were collected. For each of the variables, variance components and breeding values were estimated using the REML/BLUP procedure, which maximizes gains and considers the kinship between individuals. For that, the model 19 of SELEGEN software was adopted, which is applied to the evaluation of open pollinated progenies. Based on the first evaluation, at 15 months old, 96 individuals (12 families, with 8 individuals in each) with higher predicted genetic values were selected, which underwent molecular analysis via ISSR markers. The diversity values presented by the Nei index (H*) was 0.35 and by the Shannon index (I*) was 0.52, which is considered from intermediate to high genetic diversity. Results indicated great genetic differentiation between progenies (Φst = 0.1991), in addition, the percentage of genetic variation was greater within (80.1%) than between (19.9%) progenies. Subsequently, based on the second evaluation, at 21 months old, variance and mean components between the progenies were estimated. The progenies showed a statistically significant difference for the characteristics of ALT and DAS, and the general average for ALT was 1.64 m (from 0.64 to 3.38 m), while for DAS, the general average was 3.79 cm (from 1.97 to 6.05 cm). The mortality percentage was 52% and the residual coefficients of variation (CVe%) were 59.41% for ALT and 36.22% for DAS, indicating high environmental influence. Individual heritability values (h²a) were classified as moderate magnitude for ALT (0.16) and DAS (0.46) and the selection accuracy was higher for DAS (0.81) than for ALT (0.62). In the end, three individuals with higher genotypic values within 41 families of positive genetic effects were selected based on the DAS, resulting in genetic gains greater than 0.55 cm. The effective population size (Ne) corresponding to the selection of 121 individuals was 122.54. The progenies analyzed in this study reveal enormous potential to compose a seedling seed orchard, both because of the satisfactory predicted values for genetic gain, and because they present high values of genetic diversity and Ne, which minimizes the risks of inbreeding depression or vigor losses.